Effects of hydration and dehydration on physiological performance of wheat seeds - Pereira Motta, Carlos Augusto; Rodrigues da Silva, Walter (Pesquisa Agropecuaria Brasileira, 1997)
With the purpose of evaluating the effect of drying during the germinative process, wheat (Triticum aestivum L. cv. OCEPAR 7 - Batuíra) seeds were exposed to different periods of hydration, ranging from 3 to 48 hours, at intervals of three hours. The seed population of each period of hydration was separated into groups based on characteristics of the embryonic development and after that, dried up to original humidity. The samples of each group were evaluated in relation to the physiological performance. The results obtained for each group were evaluated and compared with the seeds of different groups and with the original population in each treatment. The analysis of the results allowed the following conclusions: the best performance and tolerance to dehydration are found in seeds that reach a more advanced development stage in a shorter period of hydration. The emission of the primary root alone is not a suitable indicator for determination of the moment, during the germination process, in which seeds become sensitive to drying. The dehydration after the root emission resulted in the death of the primary root; however, the root development takes place after rehydration by secondary root initiations.